High Frequencies of Functional Virus-Specific CD4+ T Cells in SARS-CoV-2 Subjects With Olfactory and Taste Disorders - Mele, Dalila; Calastri, Anna; Maiorano, Eugenia; Cerino, Antonella; Sachs, Michele; Oliviero, Barbara; Mantovani, Stefania; Baldanti, Fausto; Bruno, Raffaele; Benazzo, Marco; Grifoni, Alba; Sette, Alessandro; et al. (Frontiers in Immunology, 2021)
Olfactory and taste disorders (OTD) are commonly found as presenting symptoms of SARS-CoV-2 infection in patients with clinically mild COVID-19. Virus-specific T cells are thought to play an important role in the clearance of SARS-CoV-2; therefore the study of T cell specific immune responses in patients with mild symptoms may help to understand their possible role in protection from severe disease. We evaluated SARS-CoV-2-specific T cell responses to four different peptide megapools covering all SARS-CoV-2 proteins during the acute phase of the disease in 33 individuals with mild or no other symptom beside OTD and in 22 age-matched patients with severe infection. A control group of 15 outpatients with OTD and consistently negative nasopharyngeal SARS-CoV-2 RNA swabs and virus-specific IgG serology was included in the study. Increased frequencies of virus-specific CD4+ and CD8+ T cells were found in SARS-CoV-2 positive patients with OTD compared with those with severe COVID-19 and with SARS-CoV-2 negative OTD individuals. Moreover, enhanced CD4+ and CD8+ T-cell activation induced by SARS-CoV-2 peptides was associated with higher interferon (IFN)γ production. Increased frequencies of Spike (S1/S2)-specific CD4+ T cells showing enhanced IFNγ secretion and granzyme B content were associated with serum spike-specific IgG in the OTD group. In conclusion, patients with SARS-CoV-2 induced OTD develop highly functional virus-specific CD4+ and CD8+ T cells during the symptomatic phase of the disease, suggesting that robust and coordinated T-cell responses provide protection against extension of COVID-19 to the lower respiratory tract.